Specialty construction techniques for dam and levee remediation - Bruce, Donald A. (Boca Raton : CRC Press/Taylor & Francis Group, 2012)
"Dams and levees provide huge support or protection for infrastructure. They may be expensive to maintain but the cost of ignoring them can be vastly greater, as the aftermath of the 2005 Hurricane Katrina showed. System design flaws necessitate a major programme of renewal and remediation, which for Katrina alone is expected to cost around eighty billion dollars. Various specialty geotechnical processes are currently being used for dam and levee remediation. Speciality Construction Techniques for Dam and Levee Remediation deals with the construction of hydraulic cut-offs in fill, soil and rock; mainly, but not exclusively, applicable to embankment dams and levees. It then outlines how to use of prestressed rock anchors to stabilize existing concrete dams and appurtenant structures. The first main chapters follow a similar format, with an outline of the means, methods, materials and properties; illustration with case histories; quality assurance and control and verification; and then a summary of lessons learned and recommendations. The remaining main chapters are more generic and provide insight on background issues, instrumentation, specifications and contracts, and overall lessons learned.While most applicable to North America, the principles and guidance in the book apply internationally, wherever coastal structures play a significant role in protection"--
"A Spon Press Book".
Includes bibliographical references and index.
Keywords: Dams -- United States -- Maintenance and repair; Levees -- United States -- Maintenance and repair; TECHNOLOGY & ENGINEERING / Civil / Dams & Reservoirs; SCIENCE / Environmental Science